1989
DOI: 10.1161/01.cir.79.4.920
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of erythrocyte-rich and platelet-rich arterial thrombi to lysis with recombinant tissue-type plasminogen activator. A possible explanation for resistance to coronary thrombolysis.

Abstract: Acute myocardial infarction is triggered by coronary artery occlusion that may be recanalized by thrombolytic therapy with a success rate of up to 75% only. The resistance of coronary artery occlusion to thrombolysis may either be due to obstruction of the lumen by a nonthrombotic mechanism or by intrinsic resistance of thrombus to dissolution. Coronary arterial thrombi are composed of platelet-rich and erythrocyte-rich material in variable proportions. To evaluate the relative sensitivity of these thrombus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
182
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(190 citation statements)
references
References 18 publications
(6 reference statements)
7
182
0
1
Order By: Relevance
“…In response to a tPA infusion rate of 20 g ⅐ kg Ϫ1 ⅐ min Ϫ1 we observed carotid artery reperfusion in only 1 of 5 wild-type mice, results consistent with those of Jang et al, 1 who initially described the resistance of platelet-rich thrombi to lysis in rabbits. In contrast, thrombolysis was observed in 5 of 5 PAI-1 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In response to a tPA infusion rate of 20 g ⅐ kg Ϫ1 ⅐ min Ϫ1 we observed carotid artery reperfusion in only 1 of 5 wild-type mice, results consistent with those of Jang et al, 1 who initially described the resistance of platelet-rich thrombi to lysis in rabbits. In contrast, thrombolysis was observed in 5 of 5 PAI-1 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 89%
“…However, platelet-rich thrombi are highly resistant to lysis by tPA. 1 Plasminogen activator inhibitor-1 (PAI-1), 2 the primary endogenous inhibitor of tPA and urokinase, may play an important role in inhibiting arterial clot lysis. Platelets and arterial thrombi contain high concentrations of PAI-1, [3][4][5] and antibodies to PAI-1 accelerate clot lysis in vitro.…”
mentioning
confidence: 99%
“…Increasing evidence suggests that the anticoagulant effect of UFH is impaired by platelets to a greater extent than LMWH, and that platelet interaction is much more inhibited by LMWH than UFH [16][17][18]. In addition, animal models have shown that platelet-rich thrombi are particularly resistant to thrombolysis, and that platelets and fibrin still accumulate on lysing thrombi during effective thrombolytic therapy [19].…”
Section: Discussionmentioning
confidence: 99%
“…We used a rabbit femoral artery eversion graft model in which we have previously shown that stable thrombosis primarily by PR material occurs spontaneously. 21 Attempts to prevent thrombotic occlusion in this model with the use of aspirin or heparin, alone or in combination, have failed. 6 With a specific thrombin inhibitor, however, especially when combined with aspirin, it was possible not only to prevent platelet-mediated eversion graft thrombosis but also to maintain patency after disappearance of the inhibitor from blood.…”
Section: Discussionmentioning
confidence: 99%